β-catenin-driven innate and metabolic reprograming in macrophages fuel T-cell-dependent inflammation in Toxoplasma gondii infection: implications for therapeutic intervention - Kumari, Geetika; Kumar, Amit; Muduli, Rasmiranjan; Das, Mayami; Bhowmik, Prithwik; Singha, Biplab; Namdeo, Ankita; Dcosta, Criss; Wadhwa, Neerja; Maras, Jaswinder Singh; Kundu, Rakesh; Gupta, Nishith; et al. (Cell Death & Disease, 2026)
Toxoplasma gondii activates innate immunity via TLR11/12 in mice, but the lack of functional human counterparts leaves a gap in understanding parasite sensing in humans. Here, we bridge this gap by uncovering a host-intrinsic sensing mechanism, wherein beta-catenin signaling mediates immune recognition of T. gondii. Notably, this parasite hijacks the PI3K-AKT-beta-catenin pathway in macrophages to promote its replication. While beta-catenin ablation, either genetically or pharmacologically (XAV939), disavows this process, thereby inhibiting replication. Phospho-beta-catenin-TCF4 drives IRF4 transcription, followed by phosphorylation of IRF4, which regulates CYBB transcription. Augmented CYBB enhances mitochondrial-ROS and triggers mitophagy via PINK1/PARKIN, whereas ablation of beta-catenin preserves mitochondrial fitness, thereby impeding parasite growth. Enhanced ROS can oxidize host mitochondrial DNA, which then functions as a host-associated molecular pattern (HAMP). This activates the cytosolic pathogen recognition receptor (PRR) AIM2, triggering the AIM2-NLRP3-ASC-caspase-1-IL-1 beta inflammasome cascade. This cascade leads to gasdermin-D-mediated pyroptosis, a process that critically depends on the phosphorylation of beta-catenin. T. gondii's ASP5 protease plays an essential role in the phosphorylation of beta-catenin-mediated inflammasome activation. Metabolically, beta-catenin-dependent enhanced ROS stabilized HIF-1 alpha, which stimulates the HKII-LDH-A axis, promoting the Warburg effect, histone acetylation and pro-inflammatory M1-macrophage polarization (IL-12/IL-6/IL-23/TNF-alpha). beta-catenin ablation shifts metabolism to oxidative-phosphorylation, fostering M2-phenotype (IL-2/IL-10/TGF-beta) that abrogates parasites survival. beta-catenin also strengthens MHC-TCR avidity, driving Th1/Tc1, Th9/Tc9, and Th17/Tc17 paradigm, whereas beta-catenin inhibition promotes anti-inflammatory Th2/Tc2/Threg/Tcreg differentiation. Additionally, macrophage intrinsic beta-catenin dictates metabolic divergence in both CD4(+) and CD8(+)T-cells. Notably, beta-catenin-deletion in macrophages protects mice (beta-cat Delta M Phi) against infection, highlighting that XAV939 has therapeutic potential against toxoplasmosis.